Investigation on the effect of additive manufacturing processing parameters on defects of printed polymer parts - Lian, Yingsheng (Nanyang Technological University, 2021)
This report provides insights to investigation between printing parameters and defects of polymer parts through additive manufacturing process. The objective of this project is to study properties of printed parts from the Hewlett-Packard (HP) Jet Fusion Printer using HP High Reusability Polyamide 12, a variation of Nylon 12, designed specifically for use by Jet Fusion Printers. Dynamic mechanical analysis, thermomechanical analysis, and computed tomography will be employed to characterize polymetric systems. Polymer synthesis and essential characterization methods are widely covered to discover minor abnormalities variance present within separate segments throughout the multi jet fusion print bed. To obtain a more comprehensive understanding of its material behaviour, this project examines samples printed and characterized through tests exhibiting how location of the specimen produced influence on the properties of Polyamide 12 (PA-12). Through this project, discoveries of polymer characteristics and material mechanical properties can be adversely affected by poor additive manufacturing process setup or shortfall in product designing inadequacy. These may be proven by understanding and comprehending the crystalline structure, porosity, as well as its modulus capabilities at various fabrication stages to differentiate the distribution of variance found across powder printing bed of Jet Fusion Printers.